ACOUSTOSTIMULATED DIFFUSION OF GOLD ATOMS IN SILICON (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Ultrasound suppresses recombination centers in thin near-surface layers of the "input" window, (dead layers), which makes an additional contribution to the efficiency of collecting non-equilibrium charge carriers.